The effect of oral administration of Withania somnifera root on formalin-induced pain in diabetic rats - Mohsen Khalili (Basic and Clinical Neuroscience, 2009)
Abstract  Introduction: Hyperalgesia is considered as one the marked signs of subchronic diabetes mellitus that could affect the life style of the patients. With c onsidering the potential anti-diabetic effect of the medicinal plant Withania somnifera (WS)( ashwagandha), this study was designed to investigate the analgesic effect of WS on formalin-induced nociceptive responses (standard formalin test) in diabetic rats. Methods: Rats were divided into control, WS-treated control, diabetic, sodium salicylate (SS)-treated control and diabetic and WS-treated diabetic groups. For induction of diabetes, streptozotocin (STZ) was used at a single dose. The treatment groups received oral administration of ashwagandha -mixed rat pellet (6.25%) for two months.  Results: The results showed that diabetic rats exhibited a higher score of pain at both phases of the formalin test and WS-treated diabetic rats exhibited a lower nociceptive score at both phases of the test (p<0.05). Meanwhile, SS administration significantly reduced pain score only at chronic phase of the test in the diabetic group (p<0.01).   Discussion: Taken together, these results indicate that two-month administration of ashwagandha could attenuate nociceptive score in an experimental model of diabetes mellitus and this may be considered as a potential treatment for painful diabetic neuropathy.